Iskul bukol : 20 years after Ungasis and Escaleras adventure - Sotto, Vic; Sotto, Tito; De Leon, Joey; Agoncillo, Ryan; Reyes, Tony Y.; Ilacad, Orly; Sotto, Marvic C.; Tuviera, Anotonio P. ([Quezon City] OctoArts Films, 2008)
The first of the one-hour-and-a-half sitcoms, it chronicled the ups and downs of collage life in the fictional Wandbol University, where storylines ran chiefly around the doings of campus hooligans in the persons of half-siblings Tito (Tito Sotto) and Joey Escalera (Joey De Leon) that make probinsiyano Victorio Ungasis (Vic Sotto) miserable.
DVD
Executive producers, Orly R. Ilacad, Marvic S. Sotto, Antonio P. Tuviera ; Story and screenplay, Bibeth Orteza ; musical director, Michael Alba. ; director, Tony Y. Reyes.
Tito Sotto, Vic Sotto, Joel De Leon, Ryan Agoncillo.
Keywords: Iskul Bukol (Motion picture).; Comedy films; Feature films